Screening of arsenic tolerance in rice at germination and early seedling stage as influenced by sodium arsenate (Jahangirnagar University Journal of Biological Sciences, 2016)
Arsenic contamination in rice would be a serious problem for  uman  ealt . A screening program was conducted at germination and early seedling stage of rice cultivars w ic  were grown under plate culture and  ydroponic culture condition. Five different concentrations of arsenate viz.T1 (1ppm), T2 (3ppm), T3 (6ppm), T4(9ppm), T5 (12ppm) and distilled water (control) were applied on seven cultivars of rice suc  as BR-26, BRRI-28, BRRI-29, BRRI-45, BRRI-50, BR-3 and BR-14.T e germination percentage and tolerant percentage, root lengt  and s oot lengt  and biomass or seedling dry weig t decreased significantly wit  t e increase of arsenic levels.Among seven cultivars, BRRI-29 s owed t e maximum percentage of germination and tolerant percentage, BR-26 produced t e  ig est root lengt  and s oot lengt  to  ig est arsenic concentration (12 ppm) w ereas maximum biomass was obtained for BR-14.Jahangirnagar University J. Biol. Sci. 3(1): 17-26, 2014 (June)